Review of Code-Mixing in the Last Decade - Rezky Shellyanda Arnaz; Syofianis Ismail (Budapest International Research and Critics University, 2022)
The diversity of languages used by students can represent the existence of multiethnic and multilingual students. The purpose of this study reveals the choice of code in learning interactions. This research method is descriptive and qualitative using a sociolinguistic approach. Data are collected by using observation methods which include and analyzed by using the Hymes ethnographic communication method. The results of this study show that there are variations in the codes used by students, namely Indonesian (BI), foreign languages (BA), Javanese (BJ), and mixed languages (BC) in the form of code switching and mixing codes, namely from Javanese into Indonesian, mixing Javanese codes into English. The existence of internet access also helps the process of distributing information and communication to various places quickly. the use of English in the modern era requires man to open himself up for new thoughts and ideas coming from all over the world.